2019
DOI: 10.1097/rli.0000000000000590
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Time-Harmonic Elastography of the Aorta

Abstract: Objectives: The aim of this study was to investigate ultrasound time-harmonic elastography for quantifying aortic stiffness in vivo in the context of aging and arterial hypertension. Materials and Methods: Seventy-four participants (50 healthy participants and 24 participants with long-standing hypertension) were prospectively included between January 2018 and October 2018, and underwent ultrasound time-harmonic elastography of the upper abdominal aorta. Compound maps of shear-wave speed (SWS) as a surrogate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Performing time-harmonic elastography in the aorta in healthy subjects, patients and animal models, Schaafs et al reported no significant correlation between aortic stiffness indicated by shear wave speed and diameter as well as wall thickness, suggesting the possibility of using effective aortic stiffness in clinical applications. 56,57 Similar to their findings, our previous study has reported an association between the aortic stiffness obtained with and without incorporating the thickness of the wall. 20 F I G U R E 9 A, PD SNR of FB SE-EPI and FB GRE on Scanner 1.…”
Section: Discussionsupporting
confidence: 84%
“…Performing time-harmonic elastography in the aorta in healthy subjects, patients and animal models, Schaafs et al reported no significant correlation between aortic stiffness indicated by shear wave speed and diameter as well as wall thickness, suggesting the possibility of using effective aortic stiffness in clinical applications. 56,57 Similar to their findings, our previous study has reported an association between the aortic stiffness obtained with and without incorporating the thickness of the wall. 20 F I G U R E 9 A, PD SNR of FB SE-EPI and FB GRE on Scanner 1.…”
Section: Discussionsupporting
confidence: 84%
“…Mechano-sensing of WSS and other mechanical stresses in the arterial wall are of great importance 34 . The exact influence of aberrant flow and deviated WSS on mechanotransduction deserves further evaluation, considering a previously described association of aortic stiffness with aortic disease progression 35 : an interesting goal for future studies would thus be to evaluate MR methods that combine flow analysis and markers of vessel wall stiffness such as pulse wave velocity and MR elastography 36–38 …”
Section: Discussionmentioning
confidence: 99%
“…M easurement of tissue stiffness has been proven to be an accurate diagnostic marker for various diseases. [1][2][3][4][5][6][7][8] Especially, liver stiffness is an established imaging marker for hepatic diseases. [9][10][11] Liver stiffness is an intrinsic material property and can be quantified in vivo by elastography 12 and ex vivo by standardized reference methods such as shear rheomtery.…”
mentioning
confidence: 99%
“…Measurement of tissue stiffness has been proven to be an accurate diagnostic marker for various diseases 1–8 . Especially, liver stiffness is an established imaging marker for hepatic diseases 9–11 .…”
mentioning
confidence: 99%